Characteristics Burnout of Emergency Nurses at dr. Soediran Mangun Sumarso Hospital, Wonogiri - Widiyono Widiyono; Atik Aryani; Sutrisno Sutrisno; Faridha Aris Setyawan (Program Studi Keperawatan Universitas Muhammadiyah Tasikmalaya, 2023)
Nurses are vulnerable to stress because of the many responsibilities and demands that must be fulfilled and lived by nurses and overloaded work demands related to services to others. Such a situation if it continues will cause nurses to experience physical, emotional, and mental fatigue called burnout symptoms. Burnout is characterised by physical and psychological fatigue, feelings of helplessness and the development of a negative self-concept towards work and life. The purpose of this study was to describe the level of burnout in nurses in burnout nurses in the emergency room of RSUD dr. Soediran Mangun Sumarso Wonogiri. The research method used is descriptive quantitative. The population of this study was 28 nurses, the sampling technique used was total sampling. The instrument used is the Maslach Burnout Inventory (MBI) Questionnaire. The results of this study indicate that the average burnout experienced by nurses is 47.71, which has a picture of burnout on a grey signal, which means that this level shows the need to monitor the situation at hand and take action if the situation at hand gets worse. Based on the results of this study, it was found that nurses in the emergency room of RSUD dr. Soediran Mangun Sumarso Wonogiri need to be given knowledge about how to improve service quality without work pressure so that it can reduce the level of burnout in nurses and can improve the quality of hospital services in terms of providing nursing care.